Identity, agency, and the acquisition of professional language and culture - Deters, Ping (Continuum, 2011)
This book examines the relationship between identity, agency, and second language acquisition through the experiences of immigrant professionals. With globalization and the ever-increasing migration of professionals, issues related to learning an additional language and culture in professional contexts are prominent in many contemporary societies. Drawing upon data from an extensive research study of internationally educated professionals, this book examines the affordances and constraints to successful professional acculturation, and the relationships between identity, agency, and the acquisition of professional language and culture. The author provides a succinct review of socially informed theories of second language acquisition, and presents a unique analysis of identity and agency that incorporates the work of Erik Erikson and George Herbert Mead with Vygotsky's sociocultural theory and Lave and Wenger's community of practice framework. Given the pervasive problem of the underemployment of internationally educated professionals in many contemporary immigrant-receiving societies, this book makes a timely contribution that not only advances scholarship but also has important practical and policy implications.